2021
DOI: 10.1186/s40168-021-01117-7
|View full text |Cite
|
Sign up to set email alerts
|

Bog ecosystems as a playground for plant–microbe coevolution: bryophytes and vascular plants harbour functionally adapted bacteria

Abstract: Background Bogs are unique ecosystems inhabited by distinctive, coevolved assemblages of organisms, which play a global role for carbon storage, climate stability, water quality and biodiversity. To understand ecology and plant–microbe co-occurrence in bogs, we selected 12 representative species of bryophytes and vascular plants and subjected them to a shotgun metagenomic sequencing approach. We explored specific plant–microbe associations as well as functional implications of the respective co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 104 publications
4
31
0
Order By: Relevance
“…In this study, we demonstrated that a vegetation-type-based grouping of samples is a good proxy for microbiota-based PCoA clustering (Figure 5). Plant-microbe interaction is known to be a major driver of soil microbial composition in the rhizosphere [47,48]. This effect may extend to bulk soil and contribute to the changes we observed.…”
Section: Discussionmentioning
confidence: 74%
“…In this study, we demonstrated that a vegetation-type-based grouping of samples is a good proxy for microbiota-based PCoA clustering (Figure 5). Plant-microbe interaction is known to be a major driver of soil microbial composition in the rhizosphere [47,48]. This effect may extend to bulk soil and contribute to the changes we observed.…”
Section: Discussionmentioning
confidence: 74%
“…The low extant bryophyte species richness today is due to low diversification rates and massive extinction events, and especially many hornworts are still endangered from extinction. Recently it was discovered that they harbour a high, vertically transmitted microbial diversity and do not filter microorganisms out of the local environment as efficiently as vascular plants [ 22 ]. We can expect that specific AMF and other bryophyte-associated symbionts got lost in that long period; however, this topic needs further exploration.…”
Section: Resultsmentioning
confidence: 99%
“…Metagenomics data sets mentioned above were further exploited, and yielded in basic discoveries for plant microbiome science, e.g. deciphering role of Archaea on plants (Taffner et al 2018), and understanding different plant-microbiome coevolution for mosses and vascular plants [ 55 ].…”
Section: Selected Use Cases Demonstrating Added Value Of Re-using Mic...mentioning
confidence: 99%